2020
DOI: 10.3390/app11010156
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Exposure and the Effect of Tobacco Smoking on Urinary Fluoride Levels in Primary Aluminum Workers

Abstract: Workers in primary aluminum smelter are exposed to fluoride from cryolite (Na3AlF6) used in the electrolysis process. Post-shift urinary fluoride is considered as an appropriate index for examination of fluoride exposure. The objective of the study was to investigate the exposure to fluoride in primary aluminum smelter in Žiar nad Hronom (Slovakia) during three consecutive two-year periods between 2012 and 2018. The relationship between fluoride exposure in the occupational environment, tobacco smoking, and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…However, the post-shift urinary fluoride levels in the present study are (2.42±2.02 mg/g of crtn) comparable with the post-shift urinary floured levels (3.02±1.87 mg/g of crtn) reported in same aluminium industry workers in USA. An another study conducted in aluminium smelter workers in Slovakia reported pre and post-shift urinary fluoride levels of 0.455±0.353 mg/g of crtn and 0.957±0.686 mg/g of crtn respectively (17) . However, in the present study, fluoride levels were higher than the levels reported in aluminium smelter workers of Slovakia.…”
Section: Resultsmentioning
confidence: 92%
“…However, the post-shift urinary fluoride levels in the present study are (2.42±2.02 mg/g of crtn) comparable with the post-shift urinary floured levels (3.02±1.87 mg/g of crtn) reported in same aluminium industry workers in USA. An another study conducted in aluminium smelter workers in Slovakia reported pre and post-shift urinary fluoride levels of 0.455±0.353 mg/g of crtn and 0.957±0.686 mg/g of crtn respectively (17) . However, in the present study, fluoride levels were higher than the levels reported in aluminium smelter workers of Slovakia.…”
Section: Resultsmentioning
confidence: 92%